2014
DOI: 10.18632/oncotarget.2680
|View full text |Cite
|
Sign up to set email alerts
|

Divergent behaviors and underlying mechanisms of cell migration and invasion in non-metastatic T24 and its metastatic derivative T24T bladder cancer cell lines

Abstract: Previous studies on cancer cell invasion were primarily focused on its migration because these two events were often considered biologically equivalent. Here we found that T24T cells exhibited higher invasion but lower migration abilities than T24 cells. Expression of Rho-GDPases was much lower and expression of SOD2 was much higher in T24T cells than those in T24 cells. Indeed, knockdown of SOD2 in T24T cells can reverse the cell migration but without affecting cell invasion. We also found that SOD2 inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 73 publications
6
82
0
Order By: Relevance
“…Elevated MMP-2 levels have been reported to be of independent prognostic value in patients with BCs (33), while the other essential MMP member, such as MMP9 expression, is not correlated with tumor grade, stage, or overall survival of the patients with BC (34). Our previous study has also confirmed that up-regulation of MMP-2, but not MMP9, participated in mediation of BC invasion (22). To determine whether MMP-2 is associated with ISO inhibition of human BC invasion, we evaluated the effect of ISO on MMP-2 protein expression.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Elevated MMP-2 levels have been reported to be of independent prognostic value in patients with BCs (33), while the other essential MMP member, such as MMP9 expression, is not correlated with tumor grade, stage, or overall survival of the patients with BC (34). Our previous study has also confirmed that up-regulation of MMP-2, but not MMP9, participated in mediation of BC invasion (22). To determine whether MMP-2 is associated with ISO inhibition of human BC invasion, we evaluated the effect of ISO on MMP-2 protein expression.…”
Section: Resultssupporting
confidence: 61%
“…The human metastatic BC cell line T24T, which was a lineage-related lung metastatic variant of invasive BC cell line T24 (20-22), was kindly provided by Dr. Dan Theodorescu (Departments of Urology, University of Virginia, Charlottesville, VA) (20) in 2010. All the cell lines were subjected to DNA tests and authenticated in our previous studies (4).…”
Section: Methodsmentioning
confidence: 99%
“…T24T was kindly provided by Dr. Dan Theodorescu (Department of Urology, University of Virginia, Charlottesville, VA, USA) in 2010 and used in our previous studies (4, 5, 23). The UMUC3 cells were cultured in DMEM supplemented with 10% fetal bovine serum (FBS), 2mM L-glutamine, and 25μg/ml of gentamycin and the T24T cell was cultured in a 1:1 mixture of Dulbecco’s modified Eagle’s medium (DMEM)/Ham’s F12 medium supplemented with 5% FBS, 2mM L-glutamine, and 25 μg/ml of gentamycin.…”
Section: Methodsmentioning
confidence: 99%
“…The cell extracts were subjected to SDS-polyacrylamide gels (SDS-PAGE), transferred to polyvinylidene fluoride (PVDF) membranes (Bio-Rad, Hercules, CA, USA), probed with the indicated primary antibodies, and incubated with the AP-conjugated secondary antibody. The protein band specifically bound to the primary antibody was detected by Typhoon FLA 7000 (GE Healthcare, Pittsburgh, PA, USA) using an alkaline phosphatase-linked secondary antibody and an enhanced chemifluorescence Western blotting system as described in our previous studies (5, 23). …”
Section: Methodsmentioning
confidence: 99%
“…Primary p100+/+ and p100−/− mouse embryonic fibroblasts (MEFs) were immortalized according to the modified 3T3-immortalized protocol [46]. Human bladder cancer cell line UMUC3 and T24 cells were described in our previous studies [47, 48]. All cell lines were authenticated 4 to 6 months before use by using a short tandem repeat method.…”
Section: Methodsmentioning
confidence: 99%